DETERMINANTS OF PUBLIC-PRIVATE PARTNERSHIP IMPLEMENTATION IN OIC COUNTRIES - Muhammad Rizki Siddiq; Farid Arif Wibowo; Rahmatina Awaliah Kasri (Journal of Islamic Monetary Economics and Finance, 2022)
This study examines the Private-Public Partnership (PPP) implementation for financing public infrastructure and its determinants for the case of OIC countries during the period 2015–2019. Using the fixed-effects panel model and considering public resource constraints and market, macroeconomic, institutional and cultural variables as potential factors, it documents that the regulatory quality, political stability, Islamicity Index and inflation variables positively influence the implementation of PPP for financing public infrastructure in the OIC region. Meanwhile, aid is found to negatively affect the PPP implementation. These findings suggest that PPP implementation tends to be higher in countries with good institutions, stable macroeconomic conditions, low public resources, low levels of aid and strong adherence to Islamic values. The results are expected to provide insights for policymakers and private sectors involved in the implementation of PPP in OIC countries.